THE MASS TRANSFER IN UNSTABLE COMPACT BINARY STARS - Abdulameer, Mohammed (Iraqi Journal of Science, 2024)
The 2001 outburst of WZ Sagittae has shown the most compelling evidence yet for an enhancement of the mass transfer rate from the donor star during a dwarf nova outburst in the form of hot-spot brightening. It has been shown that even in this extreme case, the brightening can be attributed to tidal heating near the interaction point of an accretion stream with the expanding edge of an eccentric accretion disc, with no need at all for an increase in the mass transfer rate. Furthermore, it has been confirmed previous suggestions that an increase in mass transfer rate through the stream damps any eccentricity in an accretion disc and suppresses the appearance of super-humps, in contradiction to observations. Tidal heating is expected to be most significant in systems with smail mass ratios. It follows that systems like WZ Sagittae which has a tiny mass ratio -are those most likely to show a brightening in the hot-spot region.